2018
DOI: 10.21042/amns.2018.1.00012
|View full text |Cite
|
Sign up to set email alerts
|

Some Improvements on Relativistic Positioning Systems

Abstract: We make some considerations about Relativistic Positioning Systems (RPS). Four satellites are needed to position a user. First of all we define the main concepts. Errors should be taken into account. Errors depend on the Jacobian transformation matrix. Its Jacobian is proportional to the tetrahedron volume whose vertexes are the four tips of the receiver-satellite unit vectors. If the four satellites are seen by the user on a circumference in the sky, then, the Jacobian and the tetrahedron volume vanish. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We also found that this periodic pattern remains unchanged. It shows that the one-minute stock price fluctuation is deeply affected by the volatility of the stock price at the same time in the previous period, while it's not just the effect of the intraday model [22][23][24]. Therefore, the research perspective of investors should not only be limited to the closing price and open price of the stock market, but should also explore the intrinsic properties of the high-frequency data and make investment decisions with the the cyclical law of autocorrelation.…”
Section: Autocorrelation Analysis Of Volatilitymentioning
confidence: 96%
“…We also found that this periodic pattern remains unchanged. It shows that the one-minute stock price fluctuation is deeply affected by the volatility of the stock price at the same time in the previous period, while it's not just the effect of the intraday model [22][23][24]. Therefore, the research perspective of investors should not only be limited to the closing price and open price of the stock market, but should also explore the intrinsic properties of the high-frequency data and make investment decisions with the the cyclical law of autocorrelation.…”
Section: Autocorrelation Analysis Of Volatilitymentioning
confidence: 96%
“…GC condition: quartz capillary column was 30 mm × 0.25 mm × 0.25 μm, started at 50 °C, then followed by a rate of 8 °C/min up to 250 °C, finally reached 300 °C at a rate of 5 °C/min. The temperature of the inlet was 250 °C, column flow was 1.0 mL/min, split ratio was 20:1, and the carrier gas was high-pure helium [20,21].…”
Section: Figure 1 Preparation and Analysis Of Chaenomeles Sinensis Lmentioning
confidence: 99%
“…The ion source and the quadrupole temperature were set to 230 °C and 150 °C, respectively. The analytical standard library was analyzed via NIST14.L [19][20][21].…”
Section: The Tds-gc-ms Analysismentioning
confidence: 99%